SCREEN BOOK VERSUS PRINTED BOOK: A COMPARATIVE STUDY ON THE INFLUENCE OF STUDENTS PERCEIVED LEARNING AT SIX SEMESTERS ON ENGLISH DEPARTMENT IN UNIVERSITY OF MUHAMMADIYAH GRESIK - Lestari, Kiki Dwi; Asari, Slamet (Jetlal, 2017)
Learning media is needed in education. Books are one of the important media. In higher education, variations of the book began to be introduced in the form of printed book (traditional) and screen book (electronic). At the University of Muhammadiyah Gresik in the English department, the two book formats are taught from the first semester to sixth semester. Student learning styles and learning outcomes are also influenced by the book and the format of what books are read by students. This is preceded by the learning felt by the students on what kind of book format is preferred. In this study, researchers look for differences in likes or lessons perceived  by students  to  screen  books  and  printed  books  at  higher  levels  of education. The sample of this study is 50 students consisting of 23 students from the morning class and 27 students from the afternoon class. Sample is taken by purposive sampling technique to facilitate the researcher to find the right subject with criterion according to this research. Data collection used in this study using questionnaires with Likert scale grading 4 points. Some statements to be answered by respondents in the form of affective questions about their feelings or perceived in learning are often referred to as self-report measure. The Z test is used to test the research hypothesis as it relates to this type of comparative study and to find out the accepted or rejected null hypothesis. The results of this study indicate that there is no significant difference between screen book and printed book on students perceived learning. This means that the two natural groups, morning class and evening class, both prefer the printed book because of the tacticle interaction factor. Of the two classes have a fondness for the screen book but not significant. Then, it can be conclude that in this study null hypothesis is accepted.